Application of PST Source based DC Link Restoration for IDVR - Ramchandra Nittala; Alivelu Parimi; K Uma Rao (Institute of Advanced Engineering and Science, 2017)
Interline Dynamic Voltage Restorer (IDVR) comprises of several Dynamic Voltage Restorers (DVRs) connected to different distribution feeders in the power system sharing common energy storage. One of the DVR provides for voltage sag compensation appearing in that feeder, while the other DVRs restore the energy in the common dc-link thus dynamically maintaining the voltage of DC link capacitor constant by importing power from the other feeders. Restoration of the DC link energy plays an important role in the capability of the individual DVR in the IDVR to mitigate deep sags with long durations. In this paper the restoration of the DC link energy of the IDVR is achieved by the utilizing the phase shifting transformers (PST) which assist the respective DVR during its power control mode. A controlled switching action is provided to choose the appropriate connection of PST to the feeders depending upon the voltage sag condition. The proposed novel concept is examined in a test power system with IDVR.